Effects of biodiesel-ethanol-diesel blends on the performance indicators of a diesel engine: A study by response surface modeling. (5th February 2019) - Khoobbakht, Golmohammad; Karimi, Mahmoud; Kheiralipour, Kamran
Highlights: Effects of biodiesel-ethanol-diesel blends, engine load and rotational speed were predicted. Response surface method was used to predict effect of BED blends, engine load & rotational speed. Quadratic models to predict response surfaces were significant at 1% probability. By increasing biodiesel & ethanol percentage, specific fuel consumption was increased. By increasing biodiesel & ethanol percentage, brake power & thermal efficiency were decreased. Abstract: The objective of the present study is to evaluate the effect of several variables, including different levels of biodiesel and ethanol in diesel blended fuel (biodiesel-ethanol-diesel blends), engine load and rotational speed, on the performance indicators of a diesel engine. Design of experiments was conducted as central composite rotatable designs using response surface method. The results showed that increasing biodiesel and/or ethanol percentages in the fuel blends caused to reduce the engine brake power. A low level of biodiesel and/or ethanol in the fuel blends could enhance the engine brake thermal efficiency in comparison with the pure diesel fuel or high level of biodiesel and/or ethanol in the diesel fuel blends. The highest value of the engine brake power occurred on the condition for pure diesel, engine load of 100% (full load) and rotational speed of 2800 rpm, whereas the highest value of thermal efficiency was observed at D83 B12 E5 blended fuel, engine load of 80% and rotational speed of 1900 rpm. However, the specific fuel consumption, with a minimum at the pure diesel, full load and engine rotational speed of 2453 rpm, increased with increment biodiesel and/or ethanol percentage in the fuel blends.